Delivery of molecular and nanoscale medicine to tumors: transport barriers and strategies - Chauhan, Vikash P; Stylianopoulos, Triantafyllos; Boucher, Yves; Jain, Rakesh K (Annual review of chemical and biomolecular engineering, 2011)
Tumors are similar to organs, with unique physiology giving rise to an unusual set of transport barriers to drug delivery. Cancer therapy is limited by nonuniform drug delivery via blood vessels, inhomogeneous drug transport into tumor interstitium from the vascular compartment, and hindered transport through tumor interstitium to the target cells. Four major abnormal physical and physiological properties contribute to these transport barriers. Accumulated solid stress compresses blood vessels to diminish the drug supply to many tumor regions. Immature vasculature with high viscous and geometric resistances and reduced pressure gradients leads to sluggish and heterogeneous blood flow in tumors to further limit drug supply. Nonfunctional lymphatics coupled with highly permeable blood vessels result in elevated hydrostatic pressure in tumors to abrogate convective drug transport from blood vessels into and throughout most of the tumor tissue. Finally, a dense structure of interstitial matrix and cells serves as a tortuous, viscous, and steric barrier to diffusion of therapeutic agents. In this review, we discuss the origins and implications of these barriers. We then highlight strategies for overcoming these barriers by modulating either drug properties or the tumor microenvironment itself to enhance the delivery and effectiveness of drugs in tumors.